High performance solutions for flow shop production scheduling - Seido Nagano, Marcelo; José Ceron Branco, Fábio; Vitor Moccellin, João (Revista Gestão da Produção Operações e Sistemas, 2009)
In this article we consider the permutational flow shop scheduling problem. A new constructive heuristic method is presented with the objective of minimizing makespan and it is compared with the best constructive heuristic methods reported in literature (NEH and NEHKK). Experiment results show that the new heuristic method provides high quality solutions in comparision with the evaluated methods for the set of Taillard test problems. Keywords: Scheduling, permutation flow shop, heuristic method.